2019
DOI: 10.1126/sciimmunol.aat0297
|View full text |Cite
|
Sign up to set email alerts
|

Clever-1 contributes to lymphocyte entry into the spleen via the red pulp

Abstract: Lymphocytes recirculate continuously between the blood and lymphoid organs, a process that is of fundamental importance for proper functioning of the immune system. The molecular mechanisms underlying lymphocyte trafficking to the spleen remain an enigma. Here, we show that lymphocytes enter the spleen preferentially from vessels in the red pulp rather than the marginal sinus or the vasculature in the white pulp. Ex vivo adhesion assays in mice and humans, together with genetic ablation of Clever-1 in mice, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…47 Similarly, downregulation of Clever-1 with small-interfering RNA (siRNA) in human monocytes resulted in the upregulation of several genes that regulate pro-inflammatory mediators, such as the chemokine CXCL13, the cytokine oncostatin M (OSM), serum amyloid A (SAA2), higher secretion of TNF-α and dampening of antigen-specific (timothy grass extract) T helper 2 (T H 2) cell responses, 38 consistent with an immunosuppressive role for Clever-1. We have also demonstrated that human placentapurified Clever-1 can directly bind both B-and CD8 T cells, and to a lesser extent CD4 T cells from mouse spleen 33 and human peripheral blood. 48 Thus, it is possible that soluble Clever-1 can directly inhibit lymphocyte activation or transmigration by binding a yet unknown ligand on B-and CD8 T cells, and does not need immunosuppressive support from the type 2 macrophage.…”
Section: Potential Mechanism(s) Of Action Of Clever-1 In Tumour Growthmentioning
confidence: 69%
See 2 more Smart Citations
“…47 Similarly, downregulation of Clever-1 with small-interfering RNA (siRNA) in human monocytes resulted in the upregulation of several genes that regulate pro-inflammatory mediators, such as the chemokine CXCL13, the cytokine oncostatin M (OSM), serum amyloid A (SAA2), higher secretion of TNF-α and dampening of antigen-specific (timothy grass extract) T helper 2 (T H 2) cell responses, 38 consistent with an immunosuppressive role for Clever-1. We have also demonstrated that human placentapurified Clever-1 can directly bind both B-and CD8 T cells, and to a lesser extent CD4 T cells from mouse spleen 33 and human peripheral blood. 48 Thus, it is possible that soluble Clever-1 can directly inhibit lymphocyte activation or transmigration by binding a yet unknown ligand on B-and CD8 T cells, and does not need immunosuppressive support from the type 2 macrophage.…”
Section: Potential Mechanism(s) Of Action Of Clever-1 In Tumour Growthmentioning
confidence: 69%
“…30,31 Additional in vivo studies using mouse and rabbit models have demonstrated that Clever-1 mediates leukocyte and cancer cell trafficking via the lymphatic system into the draining lymph nodes and lymphocyte homing to the spleen. 18,32,33 Besides being able to directly bind lymphocytes, Clever-1 regulates its endothelial microenvironment. For example, the C-X-C motif chemokine ligand 13 (CXCL13) chemokine, attracting B cells on the splenic red pulp vessels, is markedly downregulated at the mRNA and protein level in the absence of Clever-1.…”
Section: Clever-1 In Homoeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that, similar to migration within lymph nodes, integrins contribute to the transmission of traction forces but are not essential for locomotion and localization. Deletion of CCR7, the receptor for the T cell attracting chemokines, had a more substantial effect, and although CCR7-deficient T cells still associated Blood-circulating naive T cells enter the spleen preferentially from vessels in the red pulp and the marginal sinus (Tadayon et al, 2019). Chaveau et al (2020) demonstrate that T cells are collected from their initial release sites and follow the outer layer of blood vessels, which serve as guidance structure to lead T cells via the marginal zone bridging channels into the T cell cortex.…”
Section: Previewsmentioning
confidence: 99%
“…Clever-1 is a scavenger receptor expressed on both afferent and efferent arms of the lymphatic vasculature and it has been demonstrated to be involved in lymphocyte and cancer cell trafficking within the lymphatics (9)(10)(11). Moreover, Clever-1 mediates trafficking of B cells and CD8 positive T cells into the splenic red pulp, but not significantly to other lymphatic organs via blood vasculature in normal conditions (12). However, it is also induced in the flat walled endothelium at sites of inflammation and in certain cancers (9,12,13).…”
Section: Introductionmentioning
confidence: 99%